Effect of Process- and Outcome-Based Financial Incentives on Weight Loss Among Prediabetic New York Medicaid Patients: A Randomized Clinical Trial. Issue 3 (March 2019) - VanEpps, Eric M.; Troxel, Andrea B.; Villamil, Elizabeth; Saulsgiver, Kathryn A.; Zhu, Jingsan; Chin, Jo-Yu; Matson, Jacqueline; Anarella, Joseph; Roohan, Patrick; Gesten, Foster; Volpp, Kevin G.
Purpose: To determine whether different financial incentives are effective in promoting weight loss among prediabetic Medicaid recipients. Design: Four-group, multicenter, randomized clinical trial. Setting and Participants: Medicaid managed care enrollees residing in New York, aged 18 to 64 years, and diagnosed as prediabetic or high risk for diabetes (N = 703). Intervention: In a 16-week program, participants were randomly assigned to one of 4 arms: (1) control (no incentives), (2) process incentives for attending weekly Diabetes Prevention Program sessions, (3) outcome incentives for achieving weekly weight loss goals, and (4) combined process and outcome incentives. Measures: Weight loss over a 16-week period; proportion who completed educational sessions; proportion who met weight loss goals. Analysis and Results: No intervention arm achieved greater reduction in weight than control (outcome incentive −6.6 lb [−9.1 to −4.1 lb], process incentive −7.3 lb [−9.5 to −5.1 lb], combined incentive −5.8 lb [−8.8 to −2.8 lb], control −7.9 lb [−11.1 to −4.7 lb]; all P > .29). Session attendance in the process incentive arm (50%) was significantly higher than control (31%; P < .0001) and combined incentive arms (28%; P < .0001), but not significantly higher than the outcome incentive arm (38%). Conclusion: Process incentives increased session attendance, but when combined at half strength with outcome incentives did not achieve that effect. There were no significant effects of either process or outcomes incentives on weight loss.